Forerunners of the Study and Analysis of the Basics of the Typology of Buildings and Elements of Landscape Architecture of Modern Wellness Centers - Makhamova, Makhbura; Azimova, Dilrabo (Universitas Diponegoro Publishing Group, Indonesia, 2025)
The research is dedicated to exploring the impact of landscape architecture on the quality of healthcare in modern wellness centers. The goal of the study was to conduct a literature review on the history of landscape architecture in medical facilities, analyze the findings of a study carried out at a sanatorium in Samarkand, Uzbekistan, and develop recommendations for establishing a favorable landscape architecture environment in healthcare settings. The analysis methods employed both qualitative and quantitative approaches. The research results demonstrated that landscape architecture has a positive influence on the quality of healthcare, contributing to patient relaxation and recovery, as well as enhancing the effectiveness of medical personnel. The authors' conclusions underscore the significance of landscape architecture in healthcare facilities and suggest that the development of new landscape architecture projects could substantially enhance the quality of healthcare by providing more comfortable conditions for patients and medical staff.